The implementation good public governance principles in village fund management: Case study in Sinduharjo Village Ngaglik, Sleman, DIY - Amut, Gamaliel Susabun; Sulistiyowati, Firma (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
This research is qualitative research with a case study method. This research was conducted in Sinduharjo Village, Kapanewon Ngaglik, Sleman Regency, Special Region of Yogyakarta Province. This study aimed to perceive the implementation of the principles of good public governance (GPG) in managing village funds in the Sinduharjo Village. Data collection techniques were used in the form of interviews and documentation. The data analysis technique used is a qualitative data analysis technique, according to Miles and Huberman (1984). The data analysis technique consists of three stages: data reduction, data display, and drawing conclusions/verification. The results of this study show that not all GPG principles are fully implemented by the basic principles and guidelines for implementing GPG set out in the 2008 Komite Nasional Kebijakan Governance (KNKG) document. The GPG principle that has been fully implemented in the management of village funds in the Sinduharjo Village is the principle of transparency and legal culture. Meanwhile, the GPG principles that have not been fully implemented in the management of village funds in the Sinduharjo Village are the principles of democracy, accountability, fairness, and equality